Tinjauan Yuridis Kedudukan Peraturan Pemerintah Pengganti Undang-Undang (Perppu) Dalam Menakar Negara Berada Dalam Ikhwal Kegentingan Memaksa Oleh Presiden - MOZA , Moza Dela Funika; Aryo, Aryo Akbar; Asri, Asri Muhammad Saleh (Jurnal Panorama Hukum, 2022)
Government Regulation in Lieu of Law (Perppu) is a legal product in the field of legislation issued by the President without waiting for prior approval by the House of Representatives. Perppu can be issued by the president to address conditions of urgency/State in an emergency that requires fast regulation to address the state's emergency problems. However, in the phenomenon that occurs, every Perppu issued by the president always raises pros and cons in the community. Instead of dealing with state emergencies, it tends to protect certain powers over the birth of a Perppu. Especially during the administration of President Jokowi, which also caused a commotion in the government when the President issued several Perppu. This of course needs to be reviewed from a juridical aspect whether the indicators of a State emergency interpreted by a President have certainty and legal justice for the community. This study aims to answer juridically related to the position of the Perppu in measuring the state is in the crisis of coercion by the president.